A spring steel with good isotropy and impact resistance and a method for manufacturing the same

CN122898809APending Publication Date: 2026-10-13JIANGYIN XINGCHENG GOLD MATERIALS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611050195.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

1、各向异性显著:传统弹簧钢硫含量控制在0.005~0.010%,易形成MnS夹杂;热轧时MnS被拉长成条带状,破坏基体连续性,导致横向冲击功仅为纵向的50~70%,交变载荷下易从横向开裂

Benefits of technology

(1)本发明采用“低C+高Ni-Mo-V”协同设计,不依赖高碳提强度,通过Ni提升低温韧性(降低韧脆转变温度≥30℃)、Mo抑制回火脆性、V细化晶粒,实现“强度-韧性”协同,解决传统弹簧钢高强度与高韧性难以兼顾的技术矛盾;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898809A_ABST
    Figure CN122898809A_ABST
Patent Text Reader

Abstract

This invention discloses an impact-resistant spring steel with good isotropy and its manufacturing method. The chemical composition of the spring steel, by mass percentage, is: C: 0.39~0.44%, Si: 1.50~1.80%, Mn: 0.60~0.90%, Cr: 0.70~0.95%, Ni: 1.65~2.00%, Mo: 0.30~0.45%, V: 0.05~0.10%, P: ≤0.015%, S≤0.003%, with the balance being Fe and unavoidable impurities. The manufacturing method includes hot metal pretreatment (KR mechanical stirring deep desulfurization), converter smelting (top and bottom blowing + single slag retention), LF refining (high basicity slag sulfur control), electroslag remelting (ternary slag system + small ingot), controlled rolling (two-stage controlled rolling), and quenching and tempering heat treatment (quenching + tempering). By optimizing the alloy composition and controlling ultra-low sulfur throughout the entire process, combined with electroslag remelting to improve the uniformity of the microstructure, the spring steel obtains a fine-grained tempered sorbite microstructure with a tensile strength ≥1800MPa, a transverse impact energy ≥10J at -40℃, and a transverse to longitudinal impact energy ratio ≥0.8, meeting the stringent requirements of automotive suspensions, high-stress springs for engineering machinery, and other demanding applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of spring steel material technology, specifically to an impact-resistant spring steel with good isotropy suitable for high stress and low temperature impact conditions, and its manufacturing method. It can be used in key components such as automotive suspension springs, engineering machinery shock absorber springs, and rail transit elastic elements, especially addressing the technical pain point of suppressing anisotropic fracture caused by sulfides in high stress components. Background Technology

[0002] As a key structural material for bearing alternating loads, spring steel must simultaneously meet the requirements of high strength (to ensure load-bearing capacity), high elastic limit (to avoid permanent deformation), and excellent impact resistance (to cope with sudden loads). With the development of lightweight automobiles and large-scale engineering machinery, the working stress of springs has increased to 1200~1500MPa, and cold-region applications place stringent requirements on low-temperature impact performance below -40℃, while also avoiding fracture due to localized stress concentration caused by anisotropy.

[0003] Existing technologies and spring steel varieties have the following core defects: 1. Significant anisotropy: The sulfur content of traditional spring steel is controlled at 0.005~0.010%, which easily forms MnS inclusions; during hot rolling, MnS is stretched into strips, which destroys the continuity of the matrix, resulting in the transverse impact energy being only 50~70% of the longitudinal energy, and it is easy to crack from the transverse under alternating loads.

[0004] 2. Insufficient low-temperature impact resistance: Traditional spring steel relies on high carbon (C=0.50~0.60%) to increase strength, which leads to a decrease in toughness. The impact energy at -40℃ is often less than 10J. Although some steel grades add Cr and Mn to improve hardenability, they lack the synergistic effect of toughening elements such as Ni and Mo, making it difficult to balance strength and toughness.

[0005] 3. Unstable control of ultra-low sulfur: Existing electroslag remelting mostly uses binary fluorite-alumina slag (basicity ≤4), with a desulfurization rate ≤46%; and the oxide belt of the electrode billet is introduced into the slag, which increases the oxidizing property of the slag, making it impossible to stably achieve S≤0.003%, and it is difficult to eliminate the anisotropy caused by MnS.

[0006] 4. Poor uniformity of structure: Traditional large ingot electroslag remelting has a high degree of component segregation, which leads to local performance fluctuations and further aggravates anisotropy. Summary of the Invention

[0007] The technical problem to be solved by the present invention is to provide an impact-resistant spring steel with good isotropy and its manufacturing method, which combines high strength (tensile strength ≥1800MPa), high and low temperature impact resistance (transverse impact energy ≥10J at -40℃) and good isotropy (transverse / longitudinal impact energy ratio ≥0.8) with the above-mentioned prior art, and a stable manufacturing method to meet the requirements of high stress and low temperature working conditions.

[0008] The technical solution adopted by the present invention to solve the above problems is as follows: an impact-resistant spring steel with good isotropy, wherein the spring steel, by mass percentage, comprises: C: 0.39-0.44%, Si: 1.50-1.80%, Mn: 0.60-0.90%, Cr: 0.70-0.95%, Ni: 1.65-2.00%, Mo: 0.30-0.45%, V: 0.05-0.10%, P: ≤0.015%, S≤0.003%, with the balance being Fe and unavoidable impurities.

[0009] The alloy composition design principle of this invention is as follows: C (0.39–0.44%): Moderate carbon content balances strength and toughness, forming carbides with Cr, Mo, and V (Cr 23 C6, Mo2C, and VC) enhance the elastic limit. Strength is insufficient below 0.39%, and toughness decreases significantly above 0.44%.

[0010] Si (1.50-1.80%): High silicon content improves tempering resistance (inhibits carbide precipitation) and ensures that the spring does not soften at the operating temperature (80-150℃). When the silicon content is below 1.50%, the tempering resistance is insufficient, and when it is above 1.80%, the tendency for decarburization is aggravated.

[0011] Mn (0.60–0.90%): Low manganese design reduces Mn segregation, avoids grain boundary brittleness, and refines austenite grains. Hardenability is insufficient when manganese content is below 0.60%, and segregation is exacerbated when it is above 0.90%.

[0012] Cr (0.70~0.95%): Improves hardenability (ensuring complete hardening of large-diameter springs) and enhances corrosion resistance, reducing rust in humid environments. Hardenability is insufficient when the chromium content is below 0.70%, and carbide coarsening occurs when it is above 0.95%.

[0013] Ni (1.65~2.00%): A core toughening element that lowers the ductile-brittle transition temperature by ≥30℃, improves low-temperature impact toughness, and refines martensitic laths to improve isotropy. Low-temperature toughness is insufficient when nickel content is below 1.65%, while it is too costly and results in excessive hardenability when above 2.00%.

[0014] Mo (0.30~0.45%): Suppresses temper brittleness at 400~500℃, synergistically forms complex carbides with V, and improves high-temperature strength. When the molybdenum content is below 0.30%, the suppression of temper brittleness is insufficient, and when it is above 0.45%, the carbides coarsen.

[0015] Vanadium (0.05~0.10%): A strong grain-refining element. Vanadium pins austenite grain boundaries, resulting in grain size ≤8μm. Vanadium content below 0.05% is insufficient for grain refinement, while content above 0.10% leads to carbide aggregation.

[0016] P, S (P≤0.015%, S≤0.003%): P≤0.015% avoids grain boundary brittleness; S≤0.003% reduces MnS inclusions in steel, ensuring that the volume fraction of MnS is ≤0.005%, thus eliminating the influence of banded sulfides.

[0017] The present invention also provides a method for manufacturing impact-resistant spring steel with good isotropy, the method comprising the following steps: Step 1: Pretreatment of molten iron.

[0018] The KR mechanical stirring method was used for deep desulfurization of molten iron. The desulfurizing agent was a CaO-Al2O3 composite desulfurizing agent (CaO content 75~85%, Al2O3 content 5~10%). The stirring head was inserted to a depth of 550~600mm, the initial stirring speed was 70~85rpm, and the amount of desulfurizing agent added was 1.5~2.0kg / t of molten iron. After treatment, the sulfur content of the molten iron was ≤0.003%, and the temperature was ≥1350℃. After pretreatment, the slag was removed twice. The first slag removal exposed 2 / 3~3 / 4 of the molten iron surface. After standing for 3~5 minutes, the second slag removal was carried out, and the exposure rate was ≥80%.

[0019] By using KR mechanical stirring for deep desulfurization and double slag removal operations, the sulfur content of molten iron is controlled at an extremely low level, laying the foundation for ultra-low sulfur control throughout the entire process.

[0020] Step 2: Converter smelting.

[0021] A top-and-bottom blown converter is used, with low-sulfur scrap steel (S≤0.004%) added to the molten iron pretreated in step 1, at a ratio of 85-90%. The smelting process adopts a "low-low-high" bottom blowing mode: the bottom blowing intensity is 0.025-0.030 Nm³ / min·t in the early stage (0-8 min), 0.030-0.035 Nm³ / min·t in the middle stage (8-15 min), and 0.050-0.055 Nm³ / min·t in the late stage (15 min to tapping). The final composition at tapping is controlled as follows: C: 0.38-0.42%, S≤0.004%, and temperature 1610-1630℃. Lime (S≤0.015%) is added during tapping for slag washing at a rate of 3-5 kg / t steel. After tapping, 1-2 kg / t steel of lime is added to thicken the slag, and then ≥90% of the slag is removed. By using a "low-low-high" bottom blowing mode and slag washing operation, the sulfur and oxygen content of molten steel can be effectively controlled.

[0022] Step 3: LF refining.

[0023] Add refining slag (CaO: 55-60%, Al2O3: 20-25%, CaF2: 8-12%) to the ladle at a rate of 8-10 kg / t of steel to create a high-basicity slag (CaO / SiO2 = 5.0-8.0). During the refining process, bottom-purge argon gas at a flow rate of 0.8-1.2 L / min·t and a stirring time of 15-20 min. Control the (FeO+MnO) content in the slag to ≤1.5%. If necessary, add aluminum granules (purity ≥99.5%) for deoxidation at a rate of 0.3-0.5 kg / t of steel. The final refining composition should meet the chemical composition requirements of claim 1, at a temperature of 1620-1640℃. Through high-basicity slag refining and low-oxidizing control, ensure that the purity of the molten steel meets the quality requirements of the electrode billet for electroslag remelting.

[0024] Step 4: Electroslag remelting.

[0025] Electrode billets are cast from the refined steel obtained in step 3. The surface of the electrode billets undergoes a peeling treatment (removal of oxide scale, surface roughness Ra≤12.5μm). Electroslag remelting uses a ternary slag system, with the following composition by mass percentage: fluorite 65%, alumina powder 25%, quicklime 10%, of which SiO2≤1% and C≤0.02%. A 1t round ingot crystallizer is used, with a crystallizer filling ratio of 45~50%. During the remelting process, 20~30g / t of steel-aluminum powder is added to the slag every 5 minutes to maintain slag reducing properties. The remelting current is 3500~4000A, and the voltage is 55~60V. After the electroslag ingot cools to room temperature, the flaw detection pass rate is ≥98%. Before use, the slag system from electroslag remelting undergoes a baking decarburization treatment at 800~900℃ for 4~6 hours to ensure that the C content in the slag is ≤0.02%.

[0026] Electrode billet peeling removes oxide scale, preventing it from entering the slag and increasing its oxidizing properties, thus affecting desulfurization efficiency. The ternary slag system (fluorite-alumina-quicklime) exhibits excellent desulfurization capabilities, high basicity, and a desulfurization rate of 53.4%–78%. A 1-ton ingot with a 45–50% filling ratio significantly enhances the stirring intensity of the molten pool, resulting in a compositional segregation of ≤0.05%, greatly reducing performance fluctuations and ensuring the overall uniformity of spring steel performance. Aluminum powder is added during remelting to maintain slag reducibility, prevent Ni and Mo burn-off, and ensure compositional stability.

[0027] Step 5: Controlled rolling.

[0028] The electroslag ingot is heated to 1150~1200℃ and held for 3~4 hours to ensure homogenization of the ingot. A two-stage controlled rolling process is employed: roughing stage (initial rolling temperature 1100~1150℃), with a total reduction of 50~60%, refining the austenite grains; finishing stage (initial rolling temperature ≤1000℃, finishing rolling temperature 820~850℃), rolling in the non-recrystallized austenite region, with a total reduction of 30~40%, and a cumulative total reduction ≥80%. After rolling, laminar flow cooling is used at a rate of 15~25℃ / s, cooling to 540~580℃ followed by air cooling. Through this two-stage controlled rolling process, the roughing stage fully refines the grains in the recrystallization region, while the finishing stage accumulates deformation energy in the non-recrystallization region, providing refined austenite grains (5-7μm) for subsequent heat treatment.

[0029] Step 6: Tempering and heat treatment.

[0030] The rolled spring steel is quenched: heating temperature 860~900℃, holding time 25~35min (30min for every 25mm of thickness), water quenching (water temperature 20~30℃, cooling time ≥5min), the martensite content of the steel after quenching is ≥95%; then tempering is performed: heating temperature 450~500℃, holding time 50~70min, air cooling to room temperature; after tempering, the sorbite content is ≥90%, finally obtaining fine-grained tempered sorbite structure.

[0031] By quenching and tempering heat treatment, a fine-grained tempered sorbite structure with a grain size ≤8μm is obtained, which balances high strength and high toughness and further improves isotropy.

[0032] The microstructure of the spring steel of this invention is fine-grained tempered sorbite with a grain size ≤ 8 μm; the mechanical properties meet the following requirements: tensile strength ≥ 1800 MPa, yield strength ≥ 1600 MPa, elongation ≥ 10%, reduction of area ≥ 40%, longitudinal impact energy at -40℃ ≥ 12 J, transverse impact energy at -40℃ ≥ 10 J, and the ratio of transverse to longitudinal impact energy ≥ 0.8.

[0033] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention adopts a “low C + high Ni-Mo-V” synergistic design, which does not rely on high carbon to improve strength. By improving low temperature toughness with Ni (reducing the ductile-brittle transition temperature by ≥30℃), suppressing temper brittleness with Mo, and refining grains with V, the “strength-toughness” synergy is achieved, which solves the technical contradiction that it is difficult to balance high strength and high toughness in traditional spring steel. (2) The present invention constructs a full-process sulfur control system of “KR mechanical stirring desulfurization + LF refining sulfur control + ternary slag electroslag remelting”. KR desulfurization ensures that the sulfur content of molten iron is ≤0.003%, LF refining strengthens desulfurization through high basicity slag, and ternary slag electroslag remelting further stabilizes the sulfur content at ≤0.003%, thereby eliminating the influence of strip-shaped MnS inclusions on isotropy from the source. (3) The present invention uses 1t small ingot electroslag remelting, combined with a crystallizer filling ratio of 45~50%, which significantly improves the stirring intensity of the molten pool, reduces the composition segregation to ≤0.05%, greatly reduces performance fluctuations, and ensures the overall uniformity of spring steel performance; (4) The present invention adopts a two-stage controlled rolling (rough rolling recrystallization zone + finish rolling non-recrystallization zone) with a cumulative reduction of ≥80% combined with tempering heat treatment to achieve a grain size of ≤8μm, taking into account both strength and toughness. Attached Figure Description

[0034] Figure 1 The manufacturing process flow chart of this invention.

[0035] Figure 2 Metallographic image (SEM, 5000×) of Example 1 of the present invention.

[0036] Figure 3 A comparison chart of the transverse / longitudinal impact energy ratios of Embodiment 1 and Comparative Example 60Si2Mn.

[0037] Figure 4 Statistical diagram of grain size distribution in Embodiment 1 of the present invention.

[0038] Figure 5 Comparison of SEM images of the impact fracture surfaces of Example 1 and Comparative Example 60Si2Mn. Detailed Implementation

[0039] The technical solution of the present invention will be described in more detail below with reference to preferred embodiments. However, these embodiments are merely descriptions of preferred implementations of the present invention and should not be construed as limiting the scope of the present invention. Example 1

[0040] 1. Chemical composition (mass percentage): C: 0.41%, Si: 1.65%, Mn: 0.75%, Cr: 0.85%, Ni: 1.80%, Mo: 0.38%, V: 0.08%, P: 0.012%, S: 0.0025%, balance Fe.

[0041] 2. Manufacturing steps: Hot metal pretreatment: KR stirring (stirring depth 580mm, initial speed 75rpm, after adding 1 / 2 of the desulfurizing agent, the speed is increased to 90rpm), the desulfurizing agent is CaO 80%+Al2O3 8%, the addition amount is 1.8kg / t; after double slag removal, the hot metal S=0.0028%, the temperature is 1360℃.

[0042] Converter smelting: 88% iron-to-metal ratio, low-sulfur scrap steel (S=0.003%); bottom blowing intensity: 0.028 Nm³ / min•t in the early stage, 0.032 Nm³ / min•t in the middle stage, and 0.052 Nm³ / min•t in the later stage; tapping C=0.40%, S=0.0035%, temperature 1620℃; 4 kg / t of lime slag is added during tapping and 1.5 kg / t of lime thick slag is added after the process is completed, with a slag removal rate of 92%.

[0043] LF refining: Add 9 kg / t of refining slag (CaO 58% + Al2O3 22% + CaF2 10%), bottom blow argon 1.0 L / min•t, stir for 18 min; add 0.4 kg / t of aluminum particles for deoxidation, (FeO + MnO) in the slag = 1.2%; refining endpoint S = 0.0027%, temperature 1630℃.

[0044] Electroslag remelting: The slag system consists of 65% fluorite + 25% alumina + 10% quicklime (SiO2=0.8%, C=0.015%, baked at 850℃ for 5h); the filling ratio of a 1t crystallizer is 48%, the remelting current is 3800A, the voltage is 58V, and 25g / t of aluminum powder is added every 5min; the S of the electroslag ingot is 0.0025%, and the flaw detection pass rate is 99%.

[0045] Controlled rolling forming: heating at 1180℃ for 3.5 hours; roughing rolling at 1120℃ with a reduction of 55%; finishing rolling at 980℃ and 830℃ with a reduction of 35%; laminar flow cooling at 20℃ / s, cooling to 560℃ and then air cooling.

[0046] Tempering heat treatment: 880℃ / 30min water quenching (water temperature 25℃, cooling time 6min); 480℃ / 60min air cooling.

[0047] 3. Performance Testing: Microstructure: fine-grained tempered sorbite, grain size 7 μm; Mechanical properties: tensile strength 1850MPa, yield strength 1650MPa, elongation 11.5%, reduction of area 42%; longitudinal impact energy at -40℃ 15J, transverse impact energy 12J, transverse / longitudinal ratio 0.80. Example 2

[0048] 1. Chemical composition (mass percentage): C: 0.39%, Si: 1.55%, Mn: 0.65%, Cr: 0.75%, Ni: 1.70%, Mo: 0.32%, V: 0.06%, P: 0.010%, S: 0.0022%, balance Fe.

[0049] 2. Manufacturing steps: basically the same as in Example 1, except that the finishing rolling temperature is 850℃ and the tempering temperature is 460℃.

[0050] 3. Performance Testing: Mechanical properties: tensile strength 1880MPa, yield strength 1680MPa, elongation 10.5%, reduction of area 41%; longitudinal impact energy at -40℃ 12J, transverse impact energy 10J, transverse / longitudinal ratio 0.83. Example 3

[0051] 1. Chemical composition (mass percentage): C: 0.44%, Si: 1.75%, Mn: 0.85%, Cr: 0.92%, Ni: 1.95%, Mo: 0.43%, V: 0.09%, P: 0.014%, S: 0.0028%, balance Fe.

[0052] 2. Manufacturing steps: basically the same as in Example 1, except that the quenching temperature is 900℃ and the tempering temperature is 490℃.

[0053] 3. Performance Testing: Mechanical properties: tensile strength 1820MPa, yield strength 1620MPa, elongation 12.0%, reduction of area 43%; longitudinal impact energy at -40℃ 18J, transverse impact energy 15J, transverse / longitudinal ratio 0.83.

[0054] Comparative test (traditional 60Si2Mn spring steel) Composition: C=0.62%, Si=2.0%, Mn=0.85%, S=0.008% (refer to existing technology); Process: Converter + LF + Hot Rolling + Quenching and Tempering; Performance: Tensile strength 1750MPa, longitudinal impact energy at -40℃ 8J, transverse impact energy 5J, transverse / longitudinal ratio 0.63; The embodiments of the present invention are significantly superior to traditional spring steel in terms of strength, low-temperature impact energy, and isotropy. Compared with the comparative examples, the tensile strength of the embodiments is increased by about 3-7%, the transverse impact energy is increased by about 100-200%, and the transverse / longitudinal ratio is increased from 0.63 to over 0.80.

[0055] In addition to the above embodiments, the present invention can also adjust parameters such as billet thickness and continuous casting process according to the production requirements of converters and electric furnaces of different tonnages. All technical solutions formed by equivalent transformation or equivalent substitution should fall within the protection scope of the claims of the present invention.

Claims

1. An impact-resistant spring steel with good isotropy, characterized in that: The spring steel, by mass percentage, comprises the following chemical composition: C: 0.39–0.44%, Si: 1.50–1.80%, Mn: 0.60–0.90%, Cr: 0.70–0.95%, Ni: 1.65–2.00%, Mo: 0.30–0.45%, V: 0.05–0.10%, P: ≤0.015%, S ≤0.003%, with the balance being Fe and unavoidable impurities.

2. The impact-resistant spring steel with good isotropy according to claim 1, characterized in that, The microstructure of spring steel is fine-grained tempered sorbite with a grain size ≤ 8 μm; the mechanical properties meet the following requirements: tensile strength ≥ 1800 MPa, yield strength ≥ 1600 MPa, elongation ≥ 10%, reduction of area ≥ 40%, longitudinal impact energy at -40℃ ≥ 12 J, transverse impact energy at -40℃ ≥ 10 J, and the ratio of transverse to longitudinal impact energy ≥ 0.

8.

3. A method for manufacturing impact-resistant spring steel with good isotropy as described in claim 1, characterized in that, The method includes the following steps: Step 1: Hot metal pretreatment The KR mechanical stirring method was used for deep desulfurization of molten iron. The desulfurizing agent was a CaO-Al2O3 composite desulfurizing agent. The stirring head was inserted to a depth of 550~600mm, the initial stirring speed was 70~85rpm, and the amount of desulfurizing agent added was 1.5~2.0kg / t of molten iron. After treatment, the sulfur content of the molten iron was ≤0.003%, and the temperature was ≥1350℃. Step 2: Converter smelting A top-and-bottom blown converter is used, with low-sulfur scrap steel (S≤0.004%) and molten iron pretreated in step 1 added, at a ratio of 85-90%. The smelting process adopts a "low-low-high" bottom blowing mode. The final composition at tapping is controlled as follows: C: 0.38-0.42%, S≤0.004%, temperature 1610-1630℃. During tapping, lime (S≤0.015%) is added for slag washing at a rate of 3-5 kg / t steel. After tapping, 1-2 kg / t steel of lime is added to thicken the slag, and then ≥90% of the slag is removed. Step 3: LF Refining Add refining slag to the ladle at a rate of 8-10 kg / t of steel to create high-basicity slag; during the refining process, bottom-purge argon gas at a flow rate of 0.8-1.2 L / min•t, and stir for 15-20 min; control the (FeO+MnO) content in the slag to ≤1.5%, and if necessary, add aluminum particles with a purity ≥99.5% for deoxidation at a rate of 0.3-0.5 kg / t of steel; the final refining composition meets the chemical composition requirements of claim 1, and the temperature is 1620-1640℃; Step 4: Electroslag Remelting Electrode billets were cast from the refined steel obtained in step 3. The surface of the electrode billets was peeled to remove oxide scale, and the surface roughness Ra ≤ 12.5 μm. During the remelting process, 20~30 g / t of steel-aluminum powder was added to the slag every 5 minutes to maintain the slag reducing properties. The remelting current was 3500~4000 A and the voltage was 55~60 V. After the electroslag ingot cooled to room temperature, the flaw detection pass rate was ≥ 98%. Step 5: Controlled rolling The electroslag ingot is heated to 1150~1200℃ and held for 3~4 hours. Two-stage controlled rolling is adopted: the roughing stage starts at 1100~1150℃ with a total reduction of 50~60% to refine the austenite grains; the finishing stage starts at ≤1000℃ and finishes at 820~850℃, rolling the non-recrystallized austenite zone with a total reduction of 30~40% and a cumulative total reduction of ≥80%. After rolling, laminar flow cooling is adopted at a cooling rate of 15~25℃ / s, and the ingot is air-cooled after cooling to 540~580℃. Step 6: Tempering and heat treatment The rolled spring steel is quenched: heating temperature 860~900℃, holding time 25~35min, holding time 30min for every 25mm of thickness, water quenching: water temperature 20~30℃, cooling time ≥5min; then tempering: heating temperature 450~500℃, holding time 50~70min, air cooling to room temperature.

4. The method for manufacturing an impact-resistant spring steel with good isotropy according to claim 1, characterized in that, The CaO-Al2O3 composite desulfurizer in step 1 has a CaO content of 75-85% and an Al2O3 content of 5-10%.

5. The method for manufacturing an impact-resistant spring steel with good isotropy according to claim 1, characterized in that: In step 1, after pretreatment, slag is removed twice. The first slag removal exposes 2 / 3 to 3 / 4 of the molten iron surface. After standing for 3 to 5 minutes, the slag is removed a second time, with an exposure rate of ≥80%.

6. The method for manufacturing an impact-resistant spring steel with good isotropy according to claim 1, characterized in that: In step 2, the "low-low-high" bottom blowing mode is as follows: in the early stage (0-8 min), the bottom blowing intensity is 0.025-0.030 Nm³ / min•t; in the middle stage (8-15 min), the bottom blowing intensity is 0.030-0.035 Nm³ / min•t; and in the later stage (15 min to the tapping stage), the bottom blowing intensity is 0.050-0.055 Nm³ / min•t.

7. The method for manufacturing an impact-resistant spring steel with good isotropy according to claim 1, characterized in that: In step 3, the refining slag specifically has CaO: 55~60%, Al2O3: 20~25%, and CaF2: 8~12%; the high-basicity slag has CaO / SiO2 = 5.0~8.

0.

8. The method for manufacturing an impact-resistant spring steel with good isotropy according to claim 1, characterized in that: In step 3, the slag system of electroslag remelting is baked to remove carbon before use. The baking temperature is 800~900℃ and the baking time is 4~6h to ensure that the C content in the slag is ≤0.02%.

9. A method for manufacturing an impact-resistant spring steel with good isotropy according to claim 1, characterized in that: In step 4, the electroslag remelting uses a ternary slag system, and the slag system composition by mass percentage is: fluorite 65%, alumina powder 25%, quicklime 10%, of which SiO2≤1% and C≤0.02%; the crystallizer is a 1t round ingot crystallizer with a crystallizer filling ratio of 45~50%.

10. A method for manufacturing an impact-resistant spring steel with good isotropy according to claim 1, characterized in that: In step 6, the martensite content of the steel after quenching is ≥95%, and the sorbite content after tempering is ≥90%.